Analyzing acute and daily load parameters in match situations – a comparison of classic and 3 × 3 basketball. Issue 1 (February 2023) - Willberg, Christina; Wellm, Dennis; Behringer, Michael; Zentgraf, Karen
Purpose: 3 × 3 is a variation of classic basketball (BB) that imposes new demands on both athletes and coaches. The objective of this study was to comprehensively describe similarities and differences in load structures between 3 × 3 and BB. Method: Between January 2020 and July 2021, internal and external load parameters of 90 elite BB and 3 × 3 athletes were monitored during 84 games using a local positioning system (10 Hz) and inertial movement sensors (100 Hz). Results: Male BB games last about 90 min; female games are shorter (82 min). Game duration in 3 × 3 is about 16 min. Compared with BB, 3 × 3 athletes perform more medium- and high-intensity accelerations and decelerations, explosive efforts, jumps, and changes of direction (CODs) per min. Average heart rates do not differ between the two disciplines, yet 3 × 3 games are rated as more exhausting than BB games. During a 3 × 3 tournament, no decrease in load characteristics is found in the final games. However, ratings of perceived exertion increase consecutively. Average possession duration in 3 × 3 is 5.4 s in which 1.4 passes are played. Most 2-point shots and turnovers occur in the last minutes (11 min – end) of the game. Conclusion: The findings of this study will help 3 × 3 coaches and athletes to design more effective training programmes and improve athletic performance. They indicate a need to focus on high accelerations, transitions, COD skills, and shooting under pressure in 3 × 3.